Daclatasvir and asunaprevir for genotype 1b chronic hepatitis C patients with chronic kidney disease. Issue 11 (12th April 2017) - Kondo, Chisa; Atsukawa, Masanori; Tsubota, Akihito; Shimada, Noritomo; Abe, Hiroshi; Asano, Toru; Yoshizawa, Kai; Okubo, Tomomi; Chuganji, Yoshimichi; Aizawa, Yoshio; Iio, Etsuko; Tanaka, Yasuhito; et al.
Abstract : Aim: To evaluate the efficacy and safety of daclatasvir and asunaprevir combined therapy in genotype 1b chronic hepatitis C patients with non‐dialysis chronic kidney disease (CKD). Methods: In a multicenter collaborative study, 249 patients received 60 mg daclatasvir (NS5A inhibitor) once a day and 100 mg of asunaprevir (NS3/4A protease inhibitor) twice a day for 24 weeks between September 2014 and September 2015 and were subjected to this analysis. Virological response and adverse events in non‐dialysis patients with CKD (stage 3–5, excluding 5D: dialysis), which was defined as estimated glomerular filtration rate <60 mL/min/1.73 m 2, were compared with those in patients without CKD. Results: Overall, the rates of rapid viral response, end‐of‐treatment response, and sustained virological response (SVR) were 76.7%, 91.2%, and 86.3%, respectively. Among 55 patients with CKD, the rapid viral response, end‐of‐treatment response, and SVR rates were 76.4%, 87.3%, and 83.6%, respectively. Among 194 patients without CKD, they were 76.8, 92.3, and 87.1%, respectively. There were no significant differences in the virological response rates between the two groups ( P = 0.999, 0.282, and 0.509, respectively). The baseline estimated glomerular filtration rate did not affect the achievement of SVR. The incidence of adverse events in patients with and without CKD were 21.8% and 13.9%, respectively (not significant, P = 0.142). Conclusion: The efficacy and safety of daclatasvir and asunaprevir combined therapy in genotype 1b chronic hepatitis C patients with non‐dialysis CKD are not inferior to those in patients without CKD.